2008
DOI: 10.1148/radiol.2482070974
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Floor Dysfunction: Assessment with Combined Analysis of Static and Dynamic MR Imaging Findings

Abstract: Combined analysis of static and dynamic MR images of patients with pelvic floor dysfunction allowed identification of certain structural abnormalities with specific dysfunctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 33 publications
3
43
0
1
Order By: Relevance
“…A lower magnitude of displacement is also attributed to stronger fascial attachments [36]. An MRI study confirmed fascial anatomical defects in SUI women [22]. Barbic et al [31] found that greater compliance of BN support with a delay in muscle activation and early onset of PFM activation was interpreted as a pretension of endopelvic fascia and vaginal wall tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lower magnitude of displacement is also attributed to stronger fascial attachments [36]. An MRI study confirmed fascial anatomical defects in SUI women [22]. Barbic et al [31] found that greater compliance of BN support with a delay in muscle activation and early onset of PFM activation was interpreted as a pretension of endopelvic fascia and vaginal wall tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been included in spite of the existence of exclusion criteria such as prolapse [21][22][23], being male [24], anal incontinence [22] and urge incontinence [25,26] if the data had been reported separately between the subject groups. In that case the data of only continent and SUI patients were extracted according to the a priori established criteria.…”
Section: Eligibility Criteria and Search Strategymentioning
confidence: 99%
“…Sonography has developed to include a three-dimensional dynamic anorectal ultrasonography technique (dynamic 3-DAUS) using a 360°t ransducer, automatic scanning, and high frequencies for high-resolution images to evaluate evacuation disorders affecting the posterior compartment (rectocele, intussusception, and anismus) and the middle compartment (grade III sigmoidocele/enterocele) with the advantage of being minimally invasive and radiation free. However, the learning curve is significant and the field of view limited to the posterior compartment preventing the study of the remaining compartments [24][25][26][27][28][29][30].…”
Section: How To Study and Characterize Pelvic Floor Disordersmentioning
confidence: 99%
“…Technical advances allowing acquisition of dynamic rapid MRI sequences have been applied to pelvic floor imaging which can provide objective information about disorders of the different compartments of the pelvis without ionizing radiation exposure [27][28][29][30][31]. However, because most of these exams are made supine which has less gravitational influence than sitting, underestimation of pelvic floor descent, intussusceptions, and even lack of detection of enteroceles or sigmoidoceles can occur [32,33].…”
Section: How To Study and Characterize Pelvic Floor Disordersmentioning
confidence: 99%
“…Beyond this, magnetic resonance imaging (MRI) and functional dynamic (cine-or real-time) MRI in particular have been employed to assess functional pelvic floor disorders in the female pelvis and have gained importance as a valuable diagnostic adjunct in the workup of urinary dysfunctions [2,3] . Few preliminary data have been presented using real-time MRI to describe the postoperative configuration of neobladder [4] .…”
Section: Introductionmentioning
confidence: 99%